2016
DOI: 10.1039/c5ra20872f
|View full text |Cite
|
Sign up to set email alerts
|

Getting faster: low temperature copper-mediated SARA ATRP of methacrylates, acrylates, styrene and vinyl chloride in polar media using sulfolane/water mixtures

Abstract: Supplemental activator and reducing agent atom transfer radical polymerization (SARA ATRP) of acrylates, methacrylates, styrene and vinyl chloride was successfully performed in sulfolane/water mixtures using ppm amounts of soluble copper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 19 publications
4
28
0
Order By: Relevance
“…Mechanistically, the increased rate of polymerization was due to the gradual reduction of the deactivator, X‐Cu II L + . The proposed dominant mechanism of ATRP in the presence of Cu 0 is shown in Scheme .…”
Section: Development Of Atrp Initiation Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, the increased rate of polymerization was due to the gradual reduction of the deactivator, X‐Cu II L + . The proposed dominant mechanism of ATRP in the presence of Cu 0 is shown in Scheme .…”
Section: Development Of Atrp Initiation Systemsmentioning
confidence: 99%
“…Inorganic sulfites such as Na 2 S 2 O 4 can also be used in SARA ATRP with a similar role of both reducing agents and supplemental activators …”
Section: Development Of Atrp Initiation Systemsmentioning
confidence: 99%
“…A recent study revealed an unusual increase in polarity, when DMSO/BMIM‐PF 6 /glycol mixtures are used in the SARA ATRP of MA which allows very fast and controlled polymerizations . Furthermore, the presence of water in the sulfolane reactions also contributes to an increase of the rate of polymerization catalyzed by zerovalent metals . Here, we investigated the influence of both TEG and water in the SARA ATRP of MA with Cu(0) and CuBr 2 /Me 6 TREN catalytic system at room temperature (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Aiming to avoid some important limitations of using DMSO as solvent for ATRP methods (e.g., the poor solubility of styrene), sulfolane was introduced in the ATRP arena as an “universal” and industrial solvent for SARA‐ATRP of meth(acrylate)s, styrene (Sty), and vinyl chloride (VC) …”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25] ATRP is catalyzed by transition metal complexes and many metals have been tested [26] but over the years the process has been refined to use small amounts of copper complexes with polydentate amine ligands. [27] Indeed, techniques such as initiators for continuous activator regeneration (ICAR) ATRP, [28,29] activators regenerated by electron transfer (ARGET) ATRP, [30][31][32][33] supplemental activator and reducing agent (SARA) ATRP, [34][35][36][37][38][39][40] photoATRP, [41][42][43][44] electrochemically mediated ATRP (eATRP), [45][46][47][48][49][50][51][52] mechanoATRP, [53] sono-ATRP [54][55][56][57][58] allowed well-controlled polymerizations with catalyst amounts down to parts per million levels relative to the monomer. Scheme 1 illustrates the mechanism of eATRP catalyzed by Cu complexes with multidentate nitrogen-based ligands (L).…”
Section: Introductionmentioning
confidence: 99%